Application of Reminiscence Therapy As An Improving Effort Cognitive Function of Older Age - Sigalingging, Ganda; Nasution, Zulkarnain; Sinaga, Martaulina; Ginting, Magdalena (Al Makki Publisher, 2024)
Cognitive decline in the elderly can affect their physical abilities and quality of life. Cognitive decline is often characterized by impaired memory and communication, resulting in dependence on others. This study aims to apply reminiscence therapy as an effort to improve cognitive function in the elderly. The case study was conducted using the gerontic nursing care process approach. The research subjects consisted of two elderly over 60 years old with cognitive impairment, who were evaluated using the Mini Mental State Examination (MMSE). Reminiscence therapy was implemented in 3 sessions for 2 weeks, each lasting 90 minutes. After the application of reminiscence therapy, both subjects' MMSE scores improved. The first subject showed the score increased from 15 to 21, while the second subject from 16 to 23, which showed improvement in the category of cognitive impairment. The application of reminiscence therapy is able to stimulate long-term memory and improve cognitive function in the elderly. These results are in line with previous research which shows that this therapy is effective in improving cognitive abilities and quality of life of the elderly. Reminiscence therapy is an important intervention to improve memory and cognitive function in the elderly with cognitive impairment. The application of this therapy can make a significant contribution to the care of the elderly and improve their quality of life.